PREFERENSI GURU DAN DOSEN DALAM MENYIMPAN DANA PADA BANK SYARIAH DI KOTA PALOPO (Kajian pada Lembaga Pendidikan Islam) - Abd Kadir Arno (MUAMALAH, 2014)
The purpose of this study is to analyze the preferences of teachers and lecturers in Islamic educational institutions in saving in Islamic banks. This is the primary research data obtained through a questionnaire to 136 teachers and 295 lecturers from the population of teachers and lecturers in four Islamic educational institutions (STAIN, STIEM, MAN and PMDS Datok Sulaiman) Palopo. Furthermore, the data were analyzed using multinomial logit regression models using SPSS software. The main conclusions of this study states that 1) religiosity variables simultaneously, the result, access, services, income and trust affect preferences of teachers and lecturers in saving in Islamic banks. 2) While partially namely religiosity, profit-sharing, service, influence the preferences of teachers and lecturers in saving in Islamic banks. 3) probablitas teachers and lecturers in the store and in Islamic banks by 75 percent compared to conventional banks, Islamic banks and conventional banks together